The Effectiveness of Advertising Cost Against Sales and Firm Value - Yohanes Adi Nugroho; Murti Puspita Rukmi; Perdhiansyah Perdhiansyah (Journal of Applied Accounting and Taxation, 2023)
Businesses and companies use advertising as a product promotion tool for customers. Every expenditure utilizing advertising carried out by the company is used to attract public interest in a product, which will increase product sales and ultimately impact increasing company value. This study examines the effectiveness of advertising costs and their impact on sales and company value. The research samples use data from the financial reports included in the consumer goods sector with the food and beverage sub-sector listed on the Indonesia Stock Exchange from 2018-2021. The research method is quantitative, and the sampling method is purposive. The test results show an influence between advertising costs and sales, and there is an effect between advertising costs and sales on firm value. The findings imply that advertising costs by companies can increase public awareness and then increase company sales. So, the higher advertising intensity the company carries can boost profits and increase company value in the eyes of investors or potential investors. This study found that advertising costs, besides influencing sales, also affect company value.